Membangun Keberanian sebagai Tourism English Public Speaker untuk Generasi Muda Bulukumba - Widya Rizky Pratiwi; Lukytta Gusti Acfira; Andriyansah (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
This community service aims to respond to the conditions of tourist visits to train young people to have the courage to communicate with International tourists using foreign languages, especially English. It is also time for the government and the private sector related to tourism to prepare themselves, design, and develop tourist objects to make them attractive. The implementation method used is a hybrid. 20% were indoors training and the rest 80% were outdoors practicing. The implementation stage began with the socialization stage, the registration, and the final stage was implementation. The team conducted outreach to explain the importance of mastering English in increasing tourist visits. The training provided was to practice composing ideas about images (building perceptions) by utilizing image media in the form of tourist objects. Furthermore, participants were trained to map their concepts and thoughts before speaking to make it easier to express ideas (mind mapping). Then, they try to practice speaking skills by telling stories (practice). Applying the 3:2 concept so that participants add vocabulary can help increase participant competency.